Nine Genes Mediate the Therapeutic Effects of Iodine-131 Radiotherapy in Thyroid Carcinoma Patients. (17th June 2020) - Shuwen, Han; Xi, Yang; Miao, Da; Jiamin, Xu; Jing, Zhuang; Weili, Gao
Abstract : Background . Thyroid carcinoma (THCA) is one of the most common malignancies of the endocrine system, which is usually treated by surgery combined with iodine-131 (I 131 ) radiotherapy. Aims . This study is aimed at exploring the potential targets of I 131 radiotherapy in THCA. Methods . The RNA-sequencing data of THCA in The Cancer Genome Atlas database (including 568 THCA samples) was downloaded. The differentially expressed genes (DEGs) between the tumour samples whether or not subjected to I 131 radiotherapy were identified using edgeR package. Using the WGCNA package, the module that was relevant with I 131 radiotherapy was selected. The intersection genes of the hub module nodes and the DEGs were obtained as hub genes, followed by the function and pathway enrichment analyses using the clusterProfiler package. Moreover, the protein-protein interaction (PPI) network for the hub genes was constructed using Cytoscape software. In addition, more important hub genes were analysed with function mining using the GenCLiP2 online tool. The qPCR analysis was used to verify the mRNA expression of more important hub genes in THCA tissues. Results . There were 500 DEGs (167 upregulated and 333 downregulated) between the two groups. WGCNA analysis showed that the green module (428 nodes) exhibited the most significant correlation with I 131 radiotherapy. A PPI network was built after the identification of 53 hub genes. In the PPI network, CDH5, KDR, CD34, FLT4, EMCN, FLT1, ROBO4, PTPRB, and CD93 exhibited higher degrees, which were mainly implicated in the vascular function. The relative expression of nine mRNAs in the THCA tissues treated with I 131 was lower. Conclusion . I 131 radiotherapy might exert therapeutic effects by targeting CDH5, KDR, CD34, FLT4, EMCN, FLT1, ROBO4, PTPRB, and CD93 in THCA patients.